Rebel Rulers Insurgent Governance and Civilian Life during War - Mampilly, Zachariah Cherian (Cornell University Press, 2011)
Rebel groups are often portrayed as predators, their leaders little more than warlords. In conflicts large and small, however, insurgents frequently take and hold territory, establishing sophisticated systems of governance that deliver extensive public services to civilians under their control. From police and courts, schools, hospitals, and taxation systems to more symbolic expressions such as official flags and anthems, some rebels are able to appropriate functions of the modern state, often to great effect in generating civilian compliance. Other insurgent organizations struggle to provide even the most basic services and suffer from the local unrest and international condemnation that result.Rebel Rulers is informed by Zachariah Cherian Mampilly's extensive fieldwork in rebel-controlled areas. Focusing on three insurgent organizations-the Liberation Tigers of Tamil Eelam (LTTE) in Sri Lanka, the Rally for Congolese Democracy (RCD) in Congo, and the Sudan People's Liberation Movement/Army (SPLM/A) in Sudan-Mampilly's comparative analysis shows that rebel leaders design governance systems in response to pressures from three main sources. They must take into consideration the needs of local civilians, who can challenge rebel rule in various ways. They must deal with internal factions that threaten their control. And they must respond to the transnational actors that operate in most contemporary conflict zones. The development of insurgent governments can benefit civilians even as they enable rebels to assert control over their newly attained and sometimes chaotic territories